Selective C–O bond formation via a photocatalytic radical coupling strategy: access to perfluoroalkoxylated (OR(F)) arenes and heteroarenes - Lee, Johnny W. (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
Development of an efficient process that employs commercially available and cost effective reagents for the synthesis of perfluoroalkoxylated aromatic compounds (Ar–OR(F)) remains a daunting challenge in organic synthesis. Herein, we report the first catalytic protocol using readily available perfluoroalkyl iodides (R(F)I) and N-(hetero)aryl-N-hydroxylamides to access a wide range of perfluoroalkoxylated (hetero)arenes. Mild reaction conditions allow for selective O–R(F) bond formation over a broad substrate scope and are tolerant of a wide variety of functional groups. Mechanistic studies suggest the formation and recombination of persistent N-hydroxyl radicals and transient R (F) radicals under photocatalytic reaction conditions to generate N–OR(F) compounds that rearrange to afford the desired products.